Car financing : comparison between Maybank‟s Islamic and conventional product / Nur Ainna Ezwani Mohammad Ezham - Mohammad Ezham, Nur Ainna Ezwani (Academy of Contemporary Islamic Studies (ACIS), 2016)
Malaysia is giving a high weightage on the expansion of its islamic financial institution. Malaysia has a wide range of islamic financial products which have been a great competitors to the current conventional products. Thus, this paper aims to discuss comparison between Islamic and conventional product in car financing at Maybank's, looking at the various components of the product from the application until the financing facilities. The novelty of this pages is to come out with a clear comparison between islamic and conventional products and finally suggest for improvement. In addition, customers can assess their own car financing is a more convenient and affordable and a good impact in the business of hire purchase. It also will show more clearly the differences between the two types of hire purchase financing and lastly this paper also about some methods proposed to expand financing in car hire purchase business in Maybank.